PENGARUH PENGETAHUAN PAJAK, SISTEM PEMBAYARAN ONLINE DAN TINGKAT PENGHASILAN TERHADAP PENERIMAAN PAJAK BUMI DAN BANGUNAN DENGAN SANKSI PAJAK SEBAGAI VARIABEL MODERASI - Aefa Indriany; Dini Martinda Lestari; Raden Irna Afriani (CV. ALIM'SPUBLISHING, 2024)
PBB is a tax whose revenue and arrange are carried out by the local government. The PBB revenue that does not even reach the target is currently a concern for the Serang Regency Government. This study aims to determine the effect of tax knowledge, online payment systems and income levels on tax revenues. And then to determine the moderating effect between tax knowledge, online payment systems and income levels on PBB revenues. The method used quantitative with a causal associative approach. The population are taxpayers who get SPPT as many as 410,478. The samples was determined by the Solvin formula as many as 100 respondents. The data analysis method used Moderated Regression Analysis using SmartPLS 4.0. Based on the results, the t-value is greater than 1.96 and the significance value of p-values is less than 0.05 so that partially tax knowledge, online payment systems, and income levels have a positive and significant effect on PBB revenue and the role of tax penalties can increase the influence of tax knowledge, online payment systems, and income levels have a significant effect on PBB revenue. So the conclusion is tax knowledge, online payment system, and income level have a significant effect on PBB revenue. Tax penalties are proven to positively moderate the influence of the three independent variables on PBB revenue.